Legal Protection of Nurses in Medical Action on the Basis of Delegation of Doctors - Reny Suryanti; Nyoman Serikat Putra Jaya; Pujiyono (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aims to determine the legal protection of nurses in performing medical actions on the basis ofan abundance of doctors. This study uses a sociological juridical approach by examining what is behindthe appearance of the application of laws and regulations. The type of data used is primary data, namelyresearch conducted directly in the community in the Bengkulu City General Hospital and secondary datais data obtained from a review of the literature, and analyzed by qualitative methods. The results showedthat nurses in Bengkulu City Hospital received protection from the hospital as long as the nurse carried outtheir duties in accordance with service standards, professional standards and standard operating procedures.The Indonesian National Nurses Association (PPNI) in Bengkulu City also provides legal protection in theform of defense and assistance as long as the nurse is registered as a member of the PPNI. Meanwhile, thecriminal responsibility of nurses in carrying out medical actions on the basis of the abundance of doctors inthe Bengkulu City Hospital has not been clearly regulated, because there has not been a written delegationof authority from doctors to nurses in carrying out medical actions. Pursuant to Article 55 and Article 56 ofthe Criminal Code, if it is proven that what a nurse has done on an abundance of doctors is a criminal act(offense), the nurse can be punished as the perpetrator (pleger), and the doctor as the one who ordered it.